Pendidikan Diniyah Kajian Filsafat Pendidikan Islam - Ahmad Zarkasyi (Qolamuna : Jurnal Studi Islam, 2020)
The article discusses Diniyah Education from the perspective of Islamic Education Philosophy (ontology, epistemology, and axiology). From the results of the analysis, it can be concluded from tafaqquh fiddiin working to elevate Islam's religion and enforce its shari'ah through the mastery of war strategies and the deepening of religion. Moreover, for the future is the mastery of technology and other propaganda strategies supported by the spread of Islam. Fiddiin is part of jihad in the field of Islamic education which must be carried out by Muslims and very relevant to educate Muslims and uphold religious dialogue. Keywords: Diniah education, ontology, axiological epistemology